Purchasing Decisions For Halal Product Which Are Influenced By Religiosity, Knowledge, And Awarness Study at Sharia Economics Students At The University of Jember - Wahyudi, Dwi; Wulandari, Deasy; Mahardiyanto, Agus; R. Khaleed, Syafiq Yazid (Sharia Business Management Study Program, Faculty of Economics and Islamic Business at IAIN Kediri, 2023)
This research was conducted to examine the influence of Religiosity, Knowledge and Awareness on Halal Purchase Intention Studies case of Islamic Economics Students at the University of Jember. This research focuses on students of the University's Islamic Economics Study Program who have purchased halal products. This research is classified as an explanatory research, using multiple linear regression analysis techniques which aim to determine the relationship between the variables of religiosity, knowledge and awareness of the purchasing decisions of halal products for Islamic Economics students at the University of Jember. Sampling was carried out using a non-probability sampling technique, namely purposive sampling with a sample size of 100 respondents. The results show that Religiosity, Knowledge and Awareness have a significant effect on the Decision to Purchase Halal Products of Islamic Economics students at the University of Jember.